Continuum Traffic Simulation - Sewall, J.; Wilkie, D.; Merrell, P.; Lin, M. C. (Computer graphics forum, 2010)
We present a novel method for the synthesis and animation of realistic traffic flows on large‐scale road networks. Our technique is based on a continuum model of traffic flow we extend to correctly handle lane changes and merges, as well as traffic behaviors due to changes in speed limit. We demonstrate how our method can be applied to the animation of many vehicles in a large‐scale traffic network at interactive rates and show that our method can simulate believable traffic flows on publicly‐available, real‐world road data. We furthermore demonstrate the scalability of this technique on many‐core systems.